2016
DOI: 10.1016/j.concog.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Mental and perceptual feedback in the development of creative flow

Abstract: Sketching is considered by artists and designers to be a vital tool in the creative process. However, research shows that externalisation during the creative process (i.e., sketching) is not necessary to create effectively. This study examines whether sketching may play a more important role in the subjective experience of creativity by facilitating the deeply focused, optimal state of consciousness termed 'flow' (being 'in the zone'). The study additionally explored whether sketching affects flow by easing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Studies in fine art found that artists who had intrinsic motivation and found their rewards in the making of art itself were more likely to maintain a creative practice in the long term (Carney 1986). Cseh, Phillips and Pearson (2015) suggested that flow provided a protective barrier against fatigue in task performance as they found that flow improved positive affect and maintained its level during the creative task. Moreover, they showed that flow was highly correlated with self-rated creativity but not with 3 rd person creativity ratings or objective external measures of productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in fine art found that artists who had intrinsic motivation and found their rewards in the making of art itself were more likely to maintain a creative practice in the long term (Carney 1986). Cseh, Phillips and Pearson (2015) suggested that flow provided a protective barrier against fatigue in task performance as they found that flow improved positive affect and maintained its level during the creative task. Moreover, they showed that flow was highly correlated with self-rated creativity but not with 3 rd person creativity ratings or objective external measures of productivity.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that feedback can be given in contexts where there is not a clear answer, as in during creative processes, and could be even more influential in that type of process. Recent research has been done to explore various methods of feedback, including sketching (Cseh et al, 2016) and technologyfacilitated feedback (Muis et al, 2015).…”
Section: Clear Feedbackmentioning
confidence: 99%
“…One artist told her, “You really don't know where you are going” (p. 274). In another interview study, Cseh ( 2017 ) concluded that clear goals, sense of control, and unambiguous feedback were not typically part of fine artists' flow experiences.…”
Section: Introductionmentioning
confidence: 99%